Drawing the Line Between Essential and Nonessential Interventions on Intersex Characteristics With European Health Care Professionals. Issue 1 (March 2021) - Hegarty, Peter; Prandelli, Marta; Lundberg, Tove; Liao, Lih-Mei; Creighton, Sarah; Roen, Katrina
Human rights statements on intersex characteristics distinguish legitimate "medically necessary" interventions from illegitimate normalizing ones. Ironically, this binary classification seems partially grounded in knowledge of anatomy and medical interventions; the very expertise that human rights statements challenge. Here, 23 European health professionals from specialist "disorder of sex development" (DSD) multidisciplinary teams located medical interventions on a continuum ranging from "medically essential" to nonessential poles. They explained their answers. Participants mostly described interventions on penile/scrotal, clitoral/labial, vaginal, and gonadal anatomy whose essential character was only partially grounded in anatomical variation and diagnoses. To explain what was medically necessary, health care professionals drew on lay understandings of child development, parental distress, collective opposition to medicalization, patients "coping" abilities, and patients' own choices. Concepts of "medical necessity" were grounded in a hybrid ontology of patients with intersex traits as both physical bodies and as phenomenological subjects. Challenges to medical expertise on human rights grounds are well warranted but presume a bounded and well-grounded category of "medically necessary" intervention that is discursively flexible. Psychologists' long-standing neglect of people with intersex characteristics, and the marginalization of clinical psychologists in DSD teams, may contribute to the construction of some controversial interventions as medically necessary.